Schopenhauer dans le roman. A propos de Sixtine de Remy de Gourmon. - Malinowski, Wiesław Mateusz (Studia Romanica Posnaniensia, 2003)
The subject of the paper is the mode of presence of Schopenhauer's philosophical thought in Remy de Gourmont's 1890 novel entitled Sixtine, roman de la vie cerebrale. The pessimistic premisses of the main character's extreme subjectivism are accompanied by an attempt to escape from Schopenhauerian omnipotent will to live (vouloir-vivre) through art, in this case through literary activity. Here originates the characteristic and innovative on the aesthetic ground motif of the novel in the novel in Gourmont's work.